Archaeal and bacterial glycerol dialkyl glycerol tetraether lipids in chimneys of the Lost City Hydrothermal Field - Lincoln, Sara A; Bradley, Alexander S; Newman, Sharon A; Summons, Roger E (ORGANIC GEOCHEMISTRY, 2013)
We detected archaeal and bacterial glycerol dialkyl glycerol tetraether (GDGT) lipids in carbonate chimneys of the Lost City Hydrothermal Field, an alkaline system near the mid-Atlantic Ridge. Isoprenoidal, archaeal tetraethers from this site include ``H-shaped'' GDGTs, crenarchaeol and GDGTs with 0-3 cyclopentane moieties (here referred to as GDGTs 0-3). Concentrations of GDGT-3 do not track those of GDGTs 0-2 across the sample set, suggesting that its biosynthesis may be subject to different controls. Two branched, bacterial GDGTs (brGDGTs) common in terrigenous environments were also detected. Consulting previously published surveys of microbial diversity at Lost City and literature on known precursor-product relationships, we investigated the provenance of these GDGTs. The principal source of GDGTs 0-3 is likely ANME-1 archaea, abundant at Lost City. H-shaped GDGTs are likely derived from thermophilic Methanobacteria and Thermoprotei. Marine Group I Thaumarchaea detected in Lost City chimneys are a potential source of crenarchaeol, but it is unclear whether they are autotrophic nitrifiers or representatives of a hydrothermal ecotype with different physiology. The detection of branched GDGTs, possibly synthesized by Acidobacteria at Lost City, adds to a growing body of evidence that the capacity for their biosynthesis is not restricted to acidophilic soil bacteria and that they cannot strictly be considered indicators of terrigenous contributions to marine sediments. Input of hydrothermally derived lipids has the potential to complicate paleoproxy applications based on GDGTs. We propose that H-GDGTs be viewed as indicators of hydrothermal input and that their detection in sediments warrants caution in proxy application when a hydrothermal origin for co-occurring isoprenoidal and brGDGTs cannot be excluded. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: HOV Alvin (Human Occupied Vehicle)